A Comparison of Students’ Mathematical Communication Ability taught by Contextual Teaching and Learning versus Problem Based Learning - Nasution, Khoirunnisa; Suyanto, Slamet (Jurnal Pendidikan Progresif, 2023)
Objective: This study aims to compare students' mathematical communication skills using Contextual Teaching and Learning (CTL) and Problem Based Learning (PBL) in class VII students of MTs Al-Ittihadiyah Medan. Method: This research is quantitative research, with quasi-experimental. The population numbered 178 students, the sampling technique used in this study is simple random sampling, with a total sample in this study of 54 students with details of 26 students using the CTL model and 28 students using the PBL model. This study does not use a control model class to streamline time. The data analysis used in this study is the t-test. The instrument used in this study was a math essay test consisting of ten questions with details of 5 pre-test questions and the remaining post-test questions which have been adapted to the students' mathematical communication indicators, namely presenting and visualizing mathematical problems in pictures and interpreting pictures, and presenting them in mathematical ideas (drawing), explain/write mathematical problems in written form using mathematical rules, be able to read and interpret data into mathematical models or in other words express mathematical ideas (mathematical expression). Finding: This study showed that the students' mathematical communication skills using the PBL model were significantly more effective than the CTL model. Conclusion: It shows that the problem-based learning model can be improve the skills of communication in the form argumentation in the learning mathematics Keywords: mathematical communication, contextual teaching learning (ctl), problem based learning (pbl)DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202309